Impact of Textbook Reform on the Formation of Chinese National Identity - Alina M. Nurzhayeva (National Research Mordova State University, 2021)
Introduction. A search for effective educational strategies that can form and maintain Chinese national identity is a highly relevant task for the Chinese academic community. Secondary school textbooks’ content revision has become one of the ways to solve the problem. The purpose of the article is to analyze the complex of educational and methodological materials within the framework of school education, aimed at influencing the formation of national identity in China. Materials and Methods. To study the problem, we conducted a survey, in which schoolteachers and parents of schoolchildren from the city of Lanzhou (PRC) took part. In order to identify the views of these two communities regarding the impact of the updated textbook content on the emerging identity of schoolchildren, we analyzed the personal data, and to understand the learning outcomes, we examined in detail the content and structure of new textual narratives, comparing them with previous educational materials. This helped us to identify a mechanism for developing lessons using the corpus of cultural and historical heritage, which was the essence of the reform aimed at shaping national priorities in the identity of the younger generation. Owing to the chosen methods, we were able to better understand and comprehend the role that ideological education is designed to play in the conditions of modern China. Results. The analysis showed that the updated textbooks reflect the main discourses of Confucian philosophy, fostering cultural and political identity in students. The survey showed that the increased national discourse in the content-factual part of textbooks facilitated the fostering of national identity among schoolchildren. Discussion and Conclusion. The materials of this article can be used for further research of the educational process and its influence on the development of civil society cohesion. This can be useful for polyethnic states in terms of strategic planning and development of mechanisms of construction and maintenance of national identity when drawing up educational textbooks. The results of this study may also be of interest to researchers dealing with educational problems and considering education as one of the elements that play an important role in the formation of national identity, as well as for teachers and students.